2015
DOI: 10.1371/journal.ppat.1004658
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Effective Subdominant Anti-HIV-1 CD8+ T Cells Within Entire Post-infection and Post-vaccination Immune Responses

Abstract: Defining the components of an HIV immunogen that could induce effective CD8+ T cell responses is critical to vaccine development. We addressed this question by investigating the viral targets of CD8+ T cells that potently inhibit HIV replication in vitro, as this is highly predictive of virus control in vivo. We observed broad and potent ex vivo CD8+ T cell-mediated viral inhibitory activity against a panel of HIV isolates among viremic controllers (VC, viral loads <5000 copies/ml), in contrast to unselected H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 66 publications
(123 reference statements)
2
44
0
Order By: Relevance
“…The present report demonstrated that Gag and Pol were the predominant HIV-1 proteins recognised by CD8 Tcells in both Ad5 regimen vaccinees and HIV-1 infected subjects. The correlation between the number of peptide pools recognized by CD8 Tcells and breadth of VIA (Fig 2B) supports the strategy that T-cell based vaccines should aim to increase the number of HIV-1 epitopes targeted by T-cells thereby potentially enhancing vaccine efficacy [58].The present report agrees with a report[59] describing inhibitory abilities of CD8 T-cells isolated directly from PBMC from HIV-1 infected STEP vaccinees (MRKAd5) where inhibition would be due to a combination of vaccination and natural infection. Inhibition breadth was narrow and inferior to chronically infected viremic controllers (pVL <5000/mL).However, PBMC availability limited the number of isolates tested in the majority of vaccinees to 3 or 4.…”
supporting
confidence: 91%
“…The present report demonstrated that Gag and Pol were the predominant HIV-1 proteins recognised by CD8 Tcells in both Ad5 regimen vaccinees and HIV-1 infected subjects. The correlation between the number of peptide pools recognized by CD8 Tcells and breadth of VIA (Fig 2B) supports the strategy that T-cell based vaccines should aim to increase the number of HIV-1 epitopes targeted by T-cells thereby potentially enhancing vaccine efficacy [58].The present report agrees with a report[59] describing inhibitory abilities of CD8 T-cells isolated directly from PBMC from HIV-1 infected STEP vaccinees (MRKAd5) where inhibition would be due to a combination of vaccination and natural infection. Inhibition breadth was narrow and inferior to chronically infected viremic controllers (pVL <5000/mL).However, PBMC availability limited the number of isolates tested in the majority of vaccinees to 3 or 4.…”
supporting
confidence: 91%
“…T cells must also be able to recognize the epitopes generated by reactivated cells during a short window and ideally target regions of vulnerability that are known to lead to loss of viral fitness upon CD8+ T cell attack in vivo [36]. Some of these regions were not included in the HIVconsv immunogen because they were not highly conserved; refinement of the immunogen design may be necessary to ensure boosting of the most potent CD8+ T cell responses [30,[37][38][39][40]. Analysis of the HLA class I-associated peptidome could facilitate this as we have recently shown, using tandem mass spectrometry, that the HLA class I-associated HIV-1 peptidome on primary CD4+ T cells includes a substantial proportion of epitopes that had not been described previously [41].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, it is conceivable that performing the ICC assays focused on “beneficial peptides” found to be associated with ex vivo viral inhibition, or performing the viral inhibition assay itself, could have produced different results. 30,31 …”
Section: Discussionmentioning
confidence: 99%